Preparation and Characterization of ZnO Nanocrystalline for Photovoltaic Applications Using Laser Ablation Technique - Salman, Odai N; Agool, Ibrahim R (Al-Nahrain Journal of Science, 2018)
The synthesis of ZnO nanocrystalline by laser ablation of a pure zinc metal target in pure water are presented hear. X-ray diffraction (XRD) analysis show that the ZnO nanoparticle is having crystalline wurtzite phase. Transmission electron microscopy (TEM) image illustrate that the ZnO nanoparticles is spherical shape with an average size of about 37 nm. Williamson-Hall (W-H) plot was employed to estimate the crystalline sizes and lattice strain. The optical energy gap were obtained from UV-Vis spectroscopy agreement with that obtained from Photoluminescence spectra. The blue emission were observed when excited the suspension with 335 nm. Dye-Sensitized Solar Cell (DSSC) was successfully fabricated from ZnO nanoparticle using electrostatic deposition technique.